Comparative Study on Growth and Conformation of Male Teddy Kids under Two Management Systems - Huma Rizwana; Najeeb Ullah Lail; Muhammad Haroon Baloch; Rani Abro; Syed Shehzad Ali Bukhari; Muhammad Naeem; Nasir Rajput; Faizan Shahani; Shahid Abro; Gulfam Ali Mughal; Ahmed Nawaz Tunio; Pershotum Khatri; et al. (Journal of Basic & Applied Sciences, 2016)
An experiment was conducted to compare the growth and conformation of male Teddy kids (3 months age), under two management systems during the year 2014. The kids were kept at the livestock experimental station, | department of Livestock Management, Faculty of Animal Husbandry and Veterinary Sciences, Sindh Agriculture University Tandojam. A total of twelve (12) Teddy kids were randomly divided into two groups i.e. A and B having six kids each. The kids of group A were reared under semi intensive management system (concentrates and open grazing) whereas kids of group B were kept under intensive management system (concentrates and green fodder). The duration of the experiment was eight (8) weeks and the observations for growth and conformation traits (girth, height and length) were recorded on weekly basis. The result revealed that the average body weight of kids in group A (8.29 kg) had significantly higher (P<0.05) than B (7.75 kg). Moreover, the average body conformation in respect of girth, height and length of group A kids (48.17cm, 40.5 cm and 39 cm respectively), were significantly higher (P<0.05) than the kids in group B (47.5 cm, 39.33 cm and 37.67 cm respectively). While comparing the economic aspects of kids reared under two management systems, it was noted that more net profit (Rs. 337 /kid) was earned from the kids of group A as compared to the kids of group B (Rs. 245 /kid). In conclusion, the kids reared under semi intensive management system demonstrated better performance in terms of body weight and conformation traits which were more profitable.